Grind or gamble? An experimental analysis of effort and spread seeking in contests - Ola Andersson; Håkan J. Holm; Erik Wengström (Research Institute of Industrial Economics (IFN), 2017)
We conduct a contest experiment where participants can invest in increasing both the mean and the spread of an uncertain performance variable. Subjects are treated with different prize schemes and in accordance with theory we observe substantial investments in spread. We find that both types of investments can be controlled with a three level prize scheme. However, the control is imperfect and behavior is characterized by inertia. The winner-take-all prize scheme has many disadvantages including high spread and heterogeneous behavior. The scheme where only one loser is punished appears superior; it generates high mean, low spread and is most popular.
Keywords: C7; D8; D02; D03; 330; Contest; Risk; Spread; Incentives; Institutional Choice; Experiment